Therapeutic potentials of bone marrow derived mesenchymal stem cells in averting organ damage due to rifampicin induced toxicity in animal model - Lawal, Danjuma (2018)
Being the front line medicine against tuberculosis, rifampicin has been used for quite a long period of time. Although it is still effective in killing the bacteria, the drug has been shown to be associated with many adverse effects, like liver and kidney toxicity. Investigations of toxicological effects due to rifampicin treatment have been published since 1974. Just few years after the drug became available in the market and more and more articles are still published showing its adverse effects on liver and kidney. Yet the drug is still prescribed and considered the best option. Prolong rifampicin therapy due to tuberculosis and the toxicity of the drug; coupled with the proportionate risk of kidney/liver malfunction has stressed the need for a new interventional approach. Intravenous administration of bone marrow mesenchymal stem cells along with rifampicin can yield a promising result. This is because the hepatocytes and renal cells growth factors that are known to have multiple function like stimulating antiapoptotic and antioxidant actions that can neutralized the toxicological impacts of the drug can be released by the MSCs. Also the ability of the transplanted MSCs to differentiate into liver and kidney cells can help in the organ regeneration as well. This research was design to assess the therapeutic potential of MSCs in averting organ damage due to rifampicin-induced liver and kidney toxicity on wistar rats and their progeny. Both male and female wistar rats were given the therapeutic doses of rifampicin via oral gavage (9mg/kg/day for 3month), rifampicin plus MSCs infusion intravenously 2.5x105cells (twice/month for 3-months), and a control group received normal saline only via oral gavage. Alteration in biochemical indicators like ALT, AST, total bilirubin, albumin, total cholesterol, triglycerides, LDL-cholesterol level, HDL-cholesterol level, urea, creatinine, total protein were found. Pathological changes in both liver and kidney of the rifampicin treated rats like necrosis of hepatocytes, cytoplasmic vacuolation, distended sinusoids, loss of polyhedral structure in the liver, hypertrophied of kupper cells in sinusoids, degeneration of liver cells, hypertrophy of hepatocytes, with pycnotic nuclei and deformed nuclei, disorganization of hepatocytes with lysis of cytoplasm. Pathological changes in kidney like increase in size of glomeruli and degeneration of renal tubules were also noticed. In order to determine if these effects can be transferred to their progeny, both the males and females were breed (while the treatments continue during the breeding) and the biochemical markers and the histopathological damages in the progeny were assessed. Transplanted MSCs was able to avert these effects by the release of growth factors and also by the differentiation potentials of the cells to both the liver and kidney cells. Transplanted MSCs showed a promising hepatic and renal protection against rifampicin induced toxicity in wistar rats and their progeny; as seen in both the biochemistry and histological data, therefore it can be used in conjunction with the antituberculosis drug rifampicin. Furthermore, gene expression studies revealed some genes that were either up regulated or down regulated due to the adverse effects of the drug, but were gradually returning back to their normal fold change value as a result of the stem cell treatment. It can be concluded that administration of bone marrow-derived mesenchymal stem cells have shown some modulatory, regenerative and therapeutic activity against liver and kidney injury due to prolonged rifampicin treatment in Wistar rats and their progenies as seen both in the biochemical indicators, histological assessment, cell quantification and also the gene expression studies.